Host response to Borrelia afzelii in BALB/c mice tested by immunoblotting - Žákovská, Alena; Rusňáková, Helena; Vostal, Karel (Annals of agricultural and environmental medicine, 2013)
The aim was to find if there is variability in the production of specific antibodies by BALB/c mice to certain antigens of three individual Borrelia afzelii (dead cell suspension) strains originally isolated from different sources. Analysis of the borrelian proteins immunogenicity was performed and determined to particular strains by immunoblotting. Some differences in production of specific IgM and IgG antibodies in each individual group of tested mice were found. The antigenic influence of OspA and OspC proteins appeared to be the most important for the induction of protective immune reaction. OspC was produced both in early and late infection of all individuals and OspA induced production of IgG antibodies in all groups of immunized mice.
Keywords: Borrelia burgdorferi komplex; lymeská nemoc; Male; Lyme Disease; myši inbrední BALB C; mužské pohlaví; Borrelia burgdorferi Group; Mice, Inbred BALB C; antigeny bakteriální; Immunoblotting; Animals; Antibody Specificity; specificita protilátek; zvířata; myši; protilátky bakteriální; imunoblotting; Antigens, Bacterial; Mice; Antibodies, Bacterial